INVESTIGATING CLASSROOM ACTIVITIES OF PUBLIC SPEAKING SUBJECT FOR THE SECOND SEMESTER SEMSTER STUDENTS AT PGRI SILAMPARI UNIVERSITY - Valencia, Nadila; Triyogo, Agus; Hamdan, Hamdan (ELite Journal : International Journal of Education, Language and Literature, 2024)
This research aims to determine the purpose of this study to find out how class activities are in learning public speaking. The design of this research is qualitative with descriptive method. Data collection techniques using interviews and documentation. Data analysis technique with steps: 1. identification, 2. classification, 3. description, 4. conclusion. The results of the study show that teaching lecturers use English more often in teaching, and most students can also use English. the lecturer teaches according to the lesson plan (RPS). students are very disciplined when studying. lecturers are also very disciplined time. when teaching, lecturers use cooperative learning model strategies, and use simulation, role play, and discussion methods.